(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to identify the importance of using the style of the cost on the basis of activity -oriented in time TDABC and its role in determining the cost of products more equitably and thus its impact on the policy of allocation of resources through the reverse of the changes that occur on an ongoing basis in the specification of the products and thus the change in the nature and type of operations . The research was conducted at the General Company for Textile Industries Wasit / knitting socks factory was based on research into the hypothesis main of that ( possible to calculate the cost of activities that cause the production through the time it takes to run these activities can then be re- distributed product costs more justic directing untapped resources to produce other products ) the researcher used the descriptive method in the theoreticalanalysis was adopted in the scientific researcher has found a set of recommendations including the need to adopt modern methods of determining the cost of products as a result of sophistication and complexity of operations in the diversity of constituent activities where products vary depending on the consumption of resources.